My secretly hot husband. 1 - Jungyeon; Nam, Gabi (Jungyeon. My secretly hot husband., 2024)
"A frightening...ly cute first impression! Despite being reborn into a fantasy world, Letitia's life has been anything but a fairy tale. After losing her parents at a young age, she was treated like a servant at her uncle's house and eventually sent off to a faraway land to marry the hideous and evil "Monster Lord" Erden Halstead. But once she arrives at her new home, Letitia's fear is quickly replaced by a whole slew of questions. Why is she randomly finding modern objects from her previous life? Why is her husband actually a sweetheart who loves bunnies? And most importantly...why is he so HOT?!"--